2018
DOI: 10.3126/jngmc.v16i1.24231
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Anemia: A profile of a tertiary care hospital

Abstract: Introduction: Globally, anemia is the burning health problem with significant disability associated with it. Iron deficiency anemia (IDA) is the commonest cause of anemia more so in developing and underdeveloped part of world. Normocytic anemia is the common finding following microcytic hypochromic and macrocytic in peripheral blood film study. To understand more about the type of anemia among anemic patients in our setting this study was carried out. Objectives: This study aims to see the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moreover, patients with the CC genotype had a significantly lower risk of OS reduction compared to other KIAA1524 genotypes (HR = 0.41). In silico analysis showed that the KIAA1524 gene correlates significantly with IL-6, one of the key proinflammatory cytokines, which is further evidence of the link between severe inflammation and unfavorable prognosis in MM [33].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, patients with the CC genotype had a significantly lower risk of OS reduction compared to other KIAA1524 genotypes (HR = 0.41). In silico analysis showed that the KIAA1524 gene correlates significantly with IL-6, one of the key proinflammatory cytokines, which is further evidence of the link between severe inflammation and unfavorable prognosis in MM [33].…”
Section: Discussionmentioning
confidence: 76%
“…An important phenomenon accompanying cachexia is the inflammatory process, during which the secretion of proinflammatory cytokines is observed, including IL-1β, Il-6, IL8, TNF-α, and interferon-gamma (INF-γ) [33]. Moreover, in the BM of MM patients, cancer cells stimulate the secretion of IL-1β and IL-6 [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation